Comprehensively Context-Aware Approach to Guaranteeing Multimedia Conferencing Services - Wu, Jiyan; Tian, Yue; Cheng, Bo; Shang, Yanlei (China communications, 2013)
Service-Oriented Communication （SOC） is a key research issue to enable media communications using the Service-Oriented Architecture （SOA）. Motivated by the neces- sity to guarantee the service quality of our web- based multimedia conferencing system, we pr- esent a Comprehensively Context-Aware （CoCA） approach in this paper. One major problem in the existing end-to-end Quality of Service （QoS） management solutions is that they analyse and exploit the relationships between the QoS me- trics and corresponding contexts in an isolated manner. In this paper, we propose a novel app- roach to leveraging such relationships in a comprehensive manner based on Bayesian net- works and the fuzzy set theory. This approach includes three phases： 1） information feedback and training, 2） QoS-to-context mapping, and 3） optimal context adaption. We implement the proposed CoCA in the real multimedia con- ferencing system and compare its performance with the existing bandwidth aware and play- back buffer aware schemes. Experimental re- sults show that the proposed CoCA outper- forms the competing approaches in improving the average video Peak Signal-to-Noise Ratio （PSNR）. It also exhibits good performance in preventing the playback buffer starvation.